Unsignalized Intersection Analysis (Case Study of Sukahaji - Majalengka Road Intersection) - Vindhy Lesmana Nauval; Joewono Prasetijo; Yusra Aulia Sari (LEADER: Civil Engineering and Architecture Journal, 2025)
Road users must pay close attention to traffic signs, Contributing to the safety and well-being of motorists.. Unsignalized intersections are very vulnerable road lanes and can endanger road users. Traffic accidents and congestion are problems that need more attention. Traffic intersections are a major concern for road users, and can certainly help with safety and security. At the crossroads, mountains use traffic signs traffic signs are not exclusive to other countries, as Indonesia has also adopted this practice, especially on highways. Based on this, the researchers wrote a journal entitled “Analysis of Unsignalized Intersections: Case Study of Sukahaji Majalengka Road, Sukahaji sub-district, Majalengka Regency. The objective of this journal is to investigate the contributing factors that elevate the likelihood of traffic congestion and accidents at the Sukahaji Majalengka road intersection This research took place at the intersection of Sukahaji Majalengka road, Sukahaji District, Majalengka Regency. In this research, the technique used is employed is the quantitative method. This method is used to observe and determine how many cars there are​ identify activities at the intersectionSource of information on vehicle density calculations include first and second data. The output information comes from the direct survey. to the target location using data obtained directly in the field to obtain traffic flow data. The results showed that the unsignalized intersection on Sukahaji road in Majalengka, experienced a high degree of saturation, especially during peak congestion hours. Based on the results of the analysis, it can be concluded that the unsignalized intersection on Sukahaji road in Majalengka, has a significant congestion problem that occurs due to the absence of traffic lights.